Діяльність МВС щодо забезпечення інтеграції України до Європейського Союзу - Зозуля, Є. (Схід, 2009)
У статті проаналізовано історичний досвід розвитку діяльності МВС у забезпеченні інтеграції України до ЄС, досліджено основні напрямки, форми співпраці європейських струк- тур, поліції країн Європи та органів внутрішніх справ України в забезпеченні інтеграції нашої держави до Європейського Союзу. Розглянуто конкретні напрямки реалізації програм МВС із виконання Плану дій "Україна - ЄС", упровадження євростандартів у контексті продовження реформування правоохоронної системи української держави. Автор обґрунтовує необхідність подальшої активізації діяльності МВС України щодо поглиблення й розширення відносин між Україною та Європейським Союзом і НАТО, зокрема в контексті реалізації політики загальноєвропейської безпеки та боротьби зі злочинністю. The article analyzed the historical experience of the Ministry of Internal Affairs concerning ensuring Ukraine's integration into the EU, examined the main trends and forms of cooperation between European institutions, the police of European countries and agencies of internal affairs in Ukraine with regard to ensuring integration of our country into the European Union. The concrete directions of programs realization of the Ministry of Internal Affairs concerning the Action Plan "Ukraine - EU" were considered , the implantation of European standards in the context of the continuing reform of the law enforcement system of the Ukrainian state, it was drawn the conclusion concerning necessity of the further energization of the executive branch bodies' activity, including the Ministry of Internal Affairs of Ukraine, concerning the intensification and enlargement relations between Ukraine and the European Union and NATO, particularly in the context of European security policy and the fight against crime.